Test of Antioxidant Activity of Ant Nest Plants (Myrmecodia tuberosa Jeck) Extract from Toli-Toli Sulawesi Tengah - Indra, Pande; Supriadi, Supriadi; Ijirana, Ijirana (Jurnal Akademika Kimia, 2019)
Ant nest plants have the greatest diversity in Papua, but due to the different location and climate between Papua and Sulawesi, especially Central Sulawesi, the composition and the active compound are different. Differences of plant species will give differences in the content and quality of simplicia from ant nest plants. This study aimed to determine the power of antioxidant in ant nest extract (Myrmecodia tuberosa Jeck) from Toli-Toli, Central Sulawesi. The sample of this study was taken at Labonu, Basidondo, and extracted by maceration method. The testing of antioxidant activity used DPPH (2,2-Diphenyl-1-picrihydrazyl). Antioxidant activity of ant nest extract was measured using spectrophotometry with concentration 20, 40, 60 and 80 ppm. The results showed that ant nest plant extract was classified as a very powerful antioxidant with an IC50 value of 26.84 ppm.